The analysis of the relation between social studies and primary school teachers ' levels of liking of children and their job satisfaction in terms of diverse variable - Melike Faiz; Oğuzhan Karadeniz; Melek Körükcü (Uluslararasi Insan Bilimleri Dergisi, 2016)
It is required for teachers to become individuals who love children, carry out their jobs with job satisfaction in order to raise individuals who are in tune with the times, effective, creative and produce suitable solutions to the challenges in the face of rapid changes that are experienced. In this research, within the scope of which the relation between social studies and primary school teachers' levels of liking of children and their job satisfaction is analyzed, The research is a descriptive study in comparative survey methods. In the research, it has been analyzed whether a statistically significant relation between social studies teachers' levels of liking of children and their job satisfaction exists or not, in terms of diverse variable. The study group of the research consists of totally 117 teachers, 57 of whom perform as social studies teachers and 60 as primary school teacher. Research data has been gathered by applying the "Barnett Liking of Children Scale" and "Job Satisfaction Scale" to the teachers participated in the research. In the analysis of data, Kruskal-Wallis H Test for independent samples, Mann-Whitney U Test for independent samples, simple correlation, Kolmogorov-Smirnov and Shapiro-Wilk normality tests have been used. In consequence of the research, any significant difference has not been found between teachers' levels of loving children and their ages and job seniorities. It has been determined that female teachers' levels of loving children are higher as compared to that of male teachers and primary school teachers have a stronger liking for children than social studies teachers. The result that their job satisfaction does not vary according to the teachers' age, seniority and field of study and according to gender, female teachers have experienced much job satisfaction than the male ones has been reached.
Keywords: Education; social sciences; Social studies teacher; primary school teacher; job satisfaction; liking of children; education; Social studies education; Primary school education; Economic growth; No inequality; Education; 4. Education; 8. Economic growth; 10. No inequality